2009
DOI: 10.2307/27740376
|View full text |Cite
|
Sign up to set email alerts
|

What Special Education Directors Say about RTI

Abstract: An e-mail survey of special education directors was conducted to ascertain practices related to implementation of Response to Intervention (RTI) processes in North Carolina schools. The data indicate that special education directors have information about RTI as a method of identifying students with disabilities, but there is little consensus on the procedural steps for implementation of the RTI process. Multiple professionals were named as persons to be responsible for collecting data, interpreting graphs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 33 publications
0
41
2
Order By: Relevance
“…Recent RTI adoption has brought increased attention to how RTI is implemented in practice. Overall, several recent surveys have targeted school administrators (Sansosti, Noltemeyer, & Goss, 2010;Werts, Lambert, & Carpenter, 2009;Weiner & Soodak, 2008) and school psychologists (Machek & Nelson, 2010;Sullivan & Long, 2010) to obtain their perceptions about the advantages of using RTI, the perceived challenges in implementing RTI, and preferences for professional development. Further, as districts initiate implementation of RTI, educator training and preparation has become a central issue to the effective implementation of RTI practices (Kratochwill, Voliansky, Clements, & Ball, 2007).…”
Section: Examining School Psychologists' and Teachers' Application Ofmentioning
confidence: 99%
“…Recent RTI adoption has brought increased attention to how RTI is implemented in practice. Overall, several recent surveys have targeted school administrators (Sansosti, Noltemeyer, & Goss, 2010;Werts, Lambert, & Carpenter, 2009;Weiner & Soodak, 2008) and school psychologists (Machek & Nelson, 2010;Sullivan & Long, 2010) to obtain their perceptions about the advantages of using RTI, the perceived challenges in implementing RTI, and preferences for professional development. Further, as districts initiate implementation of RTI, educator training and preparation has become a central issue to the effective implementation of RTI practices (Kratochwill, Voliansky, Clements, & Ball, 2007).…”
Section: Examining School Psychologists' and Teachers' Application Ofmentioning
confidence: 99%
“…These findings are not completely surprising because past research has shown that guidance for RTI at the high school level is sparse (e.g., Berkeley et al, 2009;Harlacher & Siler, 2011;King, Lemons, & Hill, 2012;Werts et al, 2009). The literature has yet to address the social benefits/barriers of RTI and/or the effects of this type of academic labeling (e.g., "that is an RTI kid").…”
Section: The Secondary Dilemmamentioning
confidence: 99%
“…However, in 2009, Berkeley and colleagues evaluated state policies on RTI across the country and found that states' levels of development and implementation varied widely. To illustrate, a recent survey of 46 special education directors in North Carolina (Werts, Lambert, & Carpenter, 2009) found little agreement on the procedural steps for RTI implementation. Furthermore, researchers found a serious lack of guidance for the secondary levels (i.e., middle and high school).…”
Section: Research-article2015mentioning
confidence: 99%
“…Wiener and Soodak (2008) surveyed special education administrators representing local educational agencies nationwide. Werts et al (2009) surveyed district-level special education administrators in one state. Specifically, about a third of the administrators stated that general education teachers would be responsible for implementation, a slightly larger group perceived implementation as a collaboration between general and special educators, and about 10% indicated that RTI was a special education assignment.…”
mentioning
confidence: 99%